The potential of the bullion business in accelerating financial inclusion: A theoretical review of Pegadaian’s strategic role - Nurkholifatul Maula; Najhah Barnamij (Environmental, Social, Governance and Sustainable Business, 2026)
Background:  Formalizing bullion banking in Indonesia represents a strategic financial evolution catalyzed by the Law on the Development and Strengthening of the Financial Sector (P2SK) and OJK Regulation No. 17 of 2024. This study aims to construct a macroeconomic value proposition for the bullion business scheme, identifying it as a critical driver for strengthening the "People’s Economy" (Ekonomi Kerakyatan). Literature traditionally views gold as a passive pawn commodity, yet recent shifts suggest its potential as an active gateway for the unbanked. Methods: This research utilizes a qualitative systematic literature review guided by PRISMA principles, synthesizing academic and regulatory data from 2015–2025. The theoretical framework integrates Financial Intermediation and Vulnerability-Stress-Adaptation (VSA) theories to analyze economic resilience.. Findings: The bullion ecosystem acts as a "formalization engine" capable of mobilizing 1,800 to 2,600 tons of idle household gold, potentially adding IDR 245 trillion to the national GDP and creating 1.8 million jobs. The study finds that digital fractional ownership allows micro-savers to accumulate assets starting at 0.01 grams, effectively democratizing credit for 66 million MSMEs. By using gold as a universal intermediary, PT. Pegadaian eliminates "credit rationing," protecting grassroots purchasing power against inflation as posited by VSA theory. Conclusion: Bullion banking transcends traditional services to become a strategic pillar of national sovereignty, transforming passive ornaments into active capital. This model successfully addresses the dimensions of accessibility and usage within the Indonesian inclusive economy. Novelty/Originality of this article: This study uniquely links the bullion model specifically to Ekonomi Kerakyatan, providing the first post-2025 macroeconomic projection of gold banking’s impact on Indonesia’s structural financial resilience.